(untitled) (KYAMC Journal, 2017)
Background: Post dural puncture headache is related to the size as well as type of the spinal needle used90. It is progressively reduced with the use of thinner Quincke type spinal needles. Objective: This was a Quasi-experimental study to compare the incidence of post dural puncture headache after caesarian section with spinal anaesthesia by two typys of needles named 25G and 27G Quincke varities. Methods: This study was conducted in the Department of Anaesthesiology of Shaheed Shurawardy Medical College Hospital, Dhaka. A total number of 60 adult patients with ASA physical status I & II scheduled for elective surgical caesarian section under spinal anaesthesia were enrolled in this study. Patients were randomly allocated equally, 30 in each group into two groups I and II. Patients of Group I, II received 25G and 27G quincke variety of spinal needle respectively. The randomization was double blind except for the anaesthetist performing spinal block. Patient, surgeon and the assessor in the ward was aware of the study. Spinal anaesthesia was performed with 2.0-2.5 ml 0.5% hyperbaric bupivacaine using 25G Quincke spinal needle (Group I),and 27G Quincke spinal needle (Group II) at L3-4 inter-vertebral space. Each patient was assessed daily for four consecutive days following Caesarean section. Incidence and severity of postdural puncture headache (PDPH) was recorded. Result: Seven (7) out of 60 patients developed PDPH giving an overall frequency of 11.6% (Table-2). Frequency of PDPH was 16.7% (5/30) in Group I, 6.7% (2/30) in Group II. In Group I, PDPH was mild in 3 patients (60%), moderate in 1 patient (20%) and severe in 1 patient (20%). In Group II, it was mild in 2 (100%), moderate in 0 and severe in 0 patient. Moderate and Severe PDPH was not observed with 27G Quincke spinal needle (Group II). None of the 60 patients with PDPH required an epidural blood patch. Symptoms were relieved by conventional means in all patients. Conclusion: In current practice epidural blood patch has the highest cure rate for management of PDPH and is usually very well tolerated by majority of patients. Overall, we concluded that when performing spinal anaesthesia for Caesarean section, 27G Quincke spinal needle has definite advantage over 25G Quincke spinal needles as far as frequency and severity of PDPH is concerned. Therefore we recommend routine use of the 27G Quincke spinal needle when performing spinal anaesthesia for Caesarean section. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 762-769